Sesapa : Bahasa Mantra Dalam Ritual Lokal Di Desa Bali Aga Buleleng Bali - I Nyoman Suka Ardiyasa (Purwadita : Jurnal Agama dan Budaya, 2021)
The use of local languages in carrying out religious rituals in Bali Aga is the main thing, even though Hindus generally use Mantra as their language of worship. In Bali Aga Village, especially in Pedawa Village, the use of Sesapa or Balinese Dialect Pedawa has become the main language that cannot be replaced until now. This research questions about the use of Sesapa in the implementation of religious rituals carried out in the Bali Aga Village. The method used in this research is descriptive qualitative. Data was collected by using interview and direct observation techniques. The results of this study indicate that the form of Sesapa used by the people of Desa Baliaga is in the form of Balinese dialect Pedawa which is shown to the Gods, to the Ancestors, and to the Bhutas, while the meaning of using this Sesapa is the meaning of worshiping local gods who are believed to be able to give safety and protection, the meaning of worshiping sacred places in Pedawa Village and the meaning of worshiping places that are considered higher than the village location.